The Effectiveness of Albendazole-Levamisole and Mebendazole-Levamisole on the Intensity of Trichuris trichiura Infection in Elementary School Children - Anto, Endy Juli; Siahaan, Jekson Martiar; Silitonga, Hendrika Andriana (Indonesian Journal of Medicine, 2020)
Background: Trichuris trichiura worm infection is still a major public health problem in Indonesia, especially in peripheral areas. Until now, the search for antihelmintic combinations that have a high healing ability against T. trichiura infections and in the search for truly effective worming is still being done. Albendazole and Mebendazole single doses still show limited efficacy in the treatment of T. trichuria worms. The combination of Albendazole with Levamisol can increase effectiveness, but this combination still needs further investigation. Based on that fact, it is necessary to study the effectiveness comparison of the degree of infection intensity between the treatment of Albendazol-Levamisol and Mebendazol-Levamisol against T. trichiura.Subjects and Method: A double blind randomized control trial was conducted at the State Elementary School in Medan, North Sumatera, from April to October 2019. A sample of 60 children was selected for this study. The dependent variable was the number of eggs decreased, the cure rate, and side effects. The independent variables were Albendazole 400 mg-Levamisol 50 mg/ 100 mg and Mebendazole 500 mg-Levamisol 50 mg/100 mg. The stools of elementary school children were examined using the Kato-Katz method to find eggs of T. trichiura infection. Data analysis was performed using the Chi square test. Results: Samples in the Albendazol-Levamisol and Mebendazol-Levamisol groups were 30 children, respectively. Children infected with T. trichiura consisted of 58 children of mild intensity (96.7%) and 2 children of moderate intensity (3.3%). On the results of stool examination, a significant difference in the number of eggs decreased in the two groups was obtained (p <0.001) and 96.7% was the cure rate for T. trichiura infection in the two groups of Albendazol-Levamisol and Mebendazol-Levamisol. In this study, there were no significant differences in side effects in the two treatment groups.Conclusion: Treatment of T. trichiura infection with single doses of Albendazol-Levamisol and Mebendazol-Levamisol showed that there were significant differences in the Number of Decreased Eggs. Meanwhile, for the cure rate, there was no difference between the Albendazol-Levamisol and Mebendazol-Levamisol groups.Keywords: T. trichiura, Albendazole-Levamisol, Mebendazole-LevamisolCorrespondence: Endy Juli Anto. Department of Parasitology, Faculty of Medicine, Universitas Methodist Indonesia, Medan, Indonesia. Email: dr.endyjulianto@gmail.com. Mobile: +62-823 6766-7575Indonesian Journal of Medicine (2020), 5(1): 17-23https://doi.org/10.26911/theijmed.2020.05.01.03